2011
DOI: 10.1002/app.33537
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of textile dye from aqueous solution by macroporous amino‐functionalized copolymer

Abstract: Macroporous poly(glycidyl methacrylate-coethylene glycol dimethacrylate) (PGME) was synthesized by suspension copolymerization and functionalized with diethylene triamine (PGME-deta). The effect of pH, contact time, and sorbent mass on sorption efficiency of initial and functionalized copolymer sample for removal of Acid Orange 10 dye from aqueous solutions was studied. No dye was sorbed by nonfunctionalized copolymer, indicating that sorption of Acid Orange 10 by PGME-deta is specific, through amino groups. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…For adsorption of OG on PGME-deta, the dye removal percent sharply increased up to50 mg of sorbent mass (for initial dye concentration of 50 mg L −1 ), and for masses higher than 110 mg, it gradually levelled off at 80% dye removal [25]. The percentage removal of OG with bagasse fly ash increased with the adsorbent dosage up to a certain limit and then it reached a constant value.…”
Section: Effects Of Adsorbent Dosagementioning
confidence: 89%
See 1 more Smart Citation
“…For adsorption of OG on PGME-deta, the dye removal percent sharply increased up to50 mg of sorbent mass (for initial dye concentration of 50 mg L −1 ), and for masses higher than 110 mg, it gradually levelled off at 80% dye removal [25]. The percentage removal of OG with bagasse fly ash increased with the adsorbent dosage up to a certain limit and then it reached a constant value.…”
Section: Effects Of Adsorbent Dosagementioning
confidence: 89%
“…The dye was not retained by PGME, indicating that adsorption of this dye is specific through amino groups. It was shown that PGME-deta selectively adsorbs OG from binary solution with Bezaktiv Rot reactive dye [25].…”
Section: Introductionmentioning
confidence: 99%
“…), and they are modifiable by inserting various ligands into the structure in order to produce specific sorbents (Uğuzdoğan et al 2010). Recently, macroporous crosslinked glycidyl methacrylate (GMA) copolymers have gained the attraction of the researchers and were successfully used for heavy and precious metal sorption as well as dye adsorbents (Elwakeel and Rekaby 2011;Sandić et al 2011;Chen et al 2007;Liu et al 2010). …”
Section: Introductionmentioning
confidence: 98%
“…[18][19][20] Activated carbons as adsorbents for the removal of phenolic compounds are the most widely used method for water treatment. Macroporous poly(glycidyl methacrylate-co-ethylene glycol dimethacrylate)s have been used for the removal of organic pollutants, [28][29][30] due to their chemical resistance, regenerability and reuse in adsorption processes. 5 Other adsorbents used for the removal of phenols from wastewaters are: zeolites, 2 bentonites, 3,22 organo-modified bentonites, 23 synthetic resins, 24 and different polymeric materials.…”
Section: Introductionmentioning
confidence: 99%